2002
DOI: 10.17310/ntj.2002.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Who Pays and Who Benefits? Examining the Distributional Consequences of the Georgia Lottery for Education

Abstract: This paper examines the incidence of the implicit lottery tax and the distribution of benefits from lottery-funded programs in Georgia. Georgia's lottery is unique in that revenues are earmarked for three educational programs-HOPE College Scholarships, universal pre-kindergarten, and education infrastructure. We estimate separate models of household-level lottery purchases and of household benefits from lottery-funded programs. Our estimates suggest that lower income and non-white households tend to have highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 12 publications
8
47
0
Order By: Relevance
“…28 See Clotfelter and Cook (1991), Hansen (1995), Miyazaki et al (1998), and Stranahan and Borg (1998) for examples. Even when the expenditure of lottery revenue is considered, for example, to subsidize college education, many lotteries remain regressive, as benefits are often paid disproportionately to higher-income recipients (Rubensetin and Scafidi 2002). 29 The probability effect is the marginal effect from the probit coefficient.…”
Section: Random Effects Tobit Modelmentioning
confidence: 99%
“…28 See Clotfelter and Cook (1991), Hansen (1995), Miyazaki et al (1998), and Stranahan and Borg (1998) for examples. Even when the expenditure of lottery revenue is considered, for example, to subsidize college education, many lotteries remain regressive, as benefits are often paid disproportionately to higher-income recipients (Rubensetin and Scafidi 2002). 29 The probability effect is the marginal effect from the probit coefficient.…”
Section: Random Effects Tobit Modelmentioning
confidence: 99%
“…This type of earmarking reduces concerns about fungibility of revenues and facilitates tracking of benefits to individuals. Rubenstein and Scafidi (2002) compared household spending on the Georgia lottery to estimated benefits from lottery programs in 1999. They collected household survey data on lottery purchases to examine the factors that affect the probability of playing the lottery, and average household spending, contingent on playing.…”
Section: The Distribution Of Costs and Benefitsmentioning
confidence: 99%
“…Using the results from the first-stage probit model, they estimated average household lottery spending contingent on playing and found that non-white households spend significantly more on the lottery than do white households, indicating that, while non-white households do not have a significantly higher probability of playing the lottery, they tend to spend significantly more per household when they do play. Rubenstein and Scafidi (2002) then used county-level demographic data and expenditures on lottery-funded programs to estimate average household benefits from each of the programs. They found that, overall, white and higher income households receive significantly larger benefits, on average, from lottery-funded programs, and that, of the lottery-funded programs, HOPE Scholarship benefits are the most strongly associated with household characteristics.…”
Section: The Distribution Of Costs and Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, while the implementation of state merit-based scholarships may prove politically popular, the effectiveness of such programs is still relatively unproven (Rubenstein and Scafidi 2002). While the educational and social benefits of the program-in terms of rising college attendance by low-…”
Section: Introductionmentioning
confidence: 99%